Does the Incredible Years reduce child externalizing problems through improved parenting? The role of child negative affectivity and serotonin transporter linked polymorphic region (5-HTTLPR) genotype. (24th April 2017) - Weeland, Joyce; Chhangur, Rabia R.; Jaffee, Sara R.; Van Der Giessen, Danielle; Matthys, Walter; Orobio De Castro, Bram; Overbeek, Geertjan
Abstract: In a randomized controlled trial, the Observational Randomized Controlled Trial of Childhood Differential Susceptibility (ORCHIDS study), we tested whether observed parental affect and observed and reported parenting behavior are mechanisms of change underlying the effects of the behavioral parent training program the Incredible Years (IY). Furthermore, we tested whether some children are more susceptible to these change mechanisms because of their temperamental negative affectivity and/or serotonin transporter linked polymorphic region ( 5-HTTLPR ) genotype. Participants were 387 Dutch children between 4 and 8 years of age ( M age = 6.31, SD = 1.33; 55.3% boys) and their parents. Results showed that although IY was successful in improving parenting behavior and increasing parental positive affect, these effects did not explain the significant decreases in child externalizing problems. We therefore found no evidence for changes in parenting behavior or parental affect being the putative mechanisms of IY effectiveness. Furthermore, intervention effects on child externalizing behavior were not moderated by child negative affectivity or 5-HTTLPR genotype. However, child 5-HTTLPR genotype did moderate intervention effects on negative parenting behavior. This suggests that in research on behavioral parent training programs, "what works for which parents" might also be an important question.